The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/foods9121808
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Potential and Anti-Inflammatory Activity of Soluble Polysaccharides Obtained from Soybean Residue

Abstract: In the present study, we assessed the extraction of low molecular weight soluble polysaccharides (MESP) from soybean by-products using microwave-assisted enzymatic technology and proposed the chemical structure of MESP using Fourier transform-infrared spectroscopy, gas chromatography, and 1H and 13C nuclear magnetic resonance spectrum analysis. The results suggested that MESP mainly comprised arabinose, rhamnose, and glucuronic acid with (1→4) glycosidic linkages in the backbone. Compared with inulin, MESP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Monosaccharide composition of the sample was analyzed by a gas chromatography-mass spectrometer (6890/5973N-GC/MSD, Agilent Technologies, Santa Clara, CA, USA), according to our previous paper [ 24 ]. Briefly, 10 mg of NNP-2 was dissolved in 10 mL of 3 M trifluoroacetic acid (TFA) and hydrolyzed at 100 °C for 3 h. The trimethylsilylated derivatives were cooled in an ice bath.…”
Section: Methodsmentioning
confidence: 99%
“…Monosaccharide composition of the sample was analyzed by a gas chromatography-mass spectrometer (6890/5973N-GC/MSD, Agilent Technologies, Santa Clara, CA, USA), according to our previous paper [ 24 ]. Briefly, 10 mg of NNP-2 was dissolved in 10 mL of 3 M trifluoroacetic acid (TFA) and hydrolyzed at 100 °C for 3 h. The trimethylsilylated derivatives were cooled in an ice bath.…”
Section: Methodsmentioning
confidence: 99%
“… Wang et al (2020) reported that SNPS inhibited LPS-induced TNF-α and IL-6 protein and mRNA expression levels in RAW 264.7 cells. Moreover, Le et al (2020) showed that MESP inhibits the levels of NO, TNF-α, IL-1β, IL-6, and IL-10 to reduce LPS-induced inflammatory response in macrophages. Meanwhile, Wang et al (2021) found that CGP-BG inhibited the protein levels of NO, IL-1β, IL-6, and TNF-α by LPS induction.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al (2020) reported that SNPS inhibited LPS-induced TNF-α and IL-6 protein and mRNA expression levels in RAW 264.7 cells. Moreover, Le et al (2020) showed that MESP inhibits the Therefore, it can be explained that GNP has anti-inflammation activity by inhibiting inflammatory mediators.…”
Section: Effects Of Gnp On No Ros and Inflammatory Cytokine Productionmentioning
confidence: 99%
“…Prebiotics has been previously proved to ameliorate intestinal inflammation. In vitro and in vivo studies provided using prebiotics as a therapy for IBD via their anti-inflammatory activities (Valcheva et al, 2015, Healey, 2020, Le et al 2020. The role of prebiotic fibers in reducing intestinal inflammation is associated with the stimulation of the growth of gut probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The role of prebiotic fibers in reducing intestinal inflammation is associated with the stimulation of the growth of gut probiotics. Soluble fiber dextrin reduces proinflammatory cytokine secretion such as IL-1b, IL-6, TNF-α , IL-23 and IL-12 in rodents model of colitis and IBD patients (Valcheva et al , 2015 andLe et al 2020).…”
Section: Discussionmentioning
confidence: 99%